MERETAS BATAS USIA: KOMUNIKASI INTERPERSONAL PENGHULU DALAM BIMBINGAN PRA NIKAH CALON PENGANTIN MUDA : Studi tentang Strategi Komunikasi Bimbingan Pra Nikah bagi Calon Pengantin di Bawah Umur di KUA Mowila - Alviana, Susan Savera; Raahmawati, Rahmawati (Al-MUNZIR, 2025)
This study aims to analyze the communication strategies of the Penghulu (Islamic Religious Leader) in optimizing premarital guidance for underage brides and grooms at the Mowila District Office of Religious Affairs (KUA). Using qualitative descriptive methods, data were obtained through observation, interviews, and documentation. The results indicate that the Penghulu applies informative and persuasive communication strategies, as well as an interpersonal approach through dyadic and small group communication. Supporting factors include openness, Penghulu competence, and clarity of messages. Obstacles include the closed attitude of prospective brides and grooms and unreported marriages to the KUA. These findings emphasize the importance of adaptive communication strategies to improve the effectiveness of premarital guidance, especially for underage brides and grooms.